1993
DOI: 10.1104/pp.102.4.1203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Distal Elongation Zone in the Response of Maize Roots to Auxin and Gravity

Abstract: between the meristem and the point at which rapid elongation is initiated as a special zone in which growth is nearly isodiametric. They referred to this region as the postmitotic "isodiametric" growth zone, The cells that show rapid graviinduced enhancement of elongation rate (Ishikawa et 1991) include cells in the postmitotic isodiametric growth zone (compare Baluska et al., 1990, andIshikawa et al., 1991).There is evidence that cells between the meristem and the CEZ also play a special role in the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 9 publications
7
105
0
1
Order By: Relevance
“…The length of this region thus represents about 5.5% of the entire growth zone. Subsequent studies confirmed the uniqueness of the cells located in the PIG zone, not only from a morphometrical point of view, but also on account of their specific cytological and physiological properties (Barlow et al, 1991;BaluSka et al, l992,1994BaluSka et al, l992, ,1996aBaluSka et al, l992, , 1996cIshikawa and Evans, 1992, 1993, 1995.…”
mentioning
confidence: 56%
“…The length of this region thus represents about 5.5% of the entire growth zone. Subsequent studies confirmed the uniqueness of the cells located in the PIG zone, not only from a morphometrical point of view, but also on account of their specific cytological and physiological properties (Barlow et al, 1991;BaluSka et al, l992,1994BaluSka et al, l992, ,1996aBaluSka et al, l992, , 1996cIshikawa and Evans, 1992, 1993, 1995.…”
mentioning
confidence: 56%
“…Most of the observations were of cells of the epidermis and of the two to three outermost cortex cell files (outer cortex) in the DTZ and in the middle part of the TZ, where we viewed major changes to the cytoskeleton (for additional details on zone specifications, see Sivaguru and Horst, 1998). However, the root-zone specifications of the nutrient solutiongrown seedlings may vary from those of the plants grown in humid air (Ishikawa and Evans, 1993). Hence, we cannot exclude overlapping from the DTZ to the proximal part of the meristematic zone.…”
Section: Microscopy and Image Evaluationmentioning
confidence: 99%
“…42 Actually, since 1993 it has been evidenced that cells belonging to this zone are strongly auxin-responsive and accomplish dramatic rearrangements of the cytoskeleton, being subjected to a series of fundamental changes in their cytoarchitecture. 50 A recent study conducted on maize demonstrated that the transition zone plays central roles in both sensing and adapting to root hypoxia. 51 The authors also observed that the oxygen deprivation of roots induces local NO emission in the TZ, that is essential for the successful acclimation of the entire maize root to oxygen deprivation.…”
Section: The Root Transition Zonementioning
confidence: 99%